The in vitro and in vivo Evaluation of Fenofibrate with a Self- Microemulsifying Formulation - Xiumin, Li; Man, Ge; Minzi, Lu; Yinghua, Jin; Dongqin, Quan (Current Drug Delivery, 2015)
Fenofibrate is virtually insoluble in water and is highly lipophilic, which leads to poor oral bioavailability. The purpose of this approach is to develop self-microemulsifying drug delivery system (SMEDDS) for oral bioavailability enhancement of fenofibrate. The in vitro dissolution test and pharmacokinetic behavior in beagle dogs were conducted to assess the formulation of fenofibrate in selfmicroemulsifying systems. The concentrations of fenofibrate were determined by HPLC. A crossover fashion study was performed in six fasted beagle dogs with SMEDDS formulation and commercial capsules. The results showed that SMEDDS formulation provides a good drug release with more than 90% of fenofibrate dissoluted from self-emulsifying formulations while less than 10% from the commercial capsules was released within 20min. The mean particle size of SMEDDS formulation after dispersion was about 33.7nm In pharmacokinetic parameters of SMEDDS formulation, the area under the plasma concentration-time curve (AUC) was significantly higher and was approximately 7-fold greater than that obtained when commercial capsule of the same dose of fenofibrate was administered. Also, the maximum absorption was advanced (2h to 1.25h) with SMEDDS formulation. The self-microemulsifying drug delivery systems can significantly increase fenofibrate dissolution in vitro and absorption in vivo.
Keywords: dissolution